Strategi Promosi Venue MICE Mandiri di Kota Depok Melalui Website "Nyok Ke Depok" - Amadea Saraswati; Firman Syah (Bisnis Event, 2023)
Promotional activities are very important to inform tourist destinations and MICE to the wider community. Promotional activities can be carried out through various media, none other than print media or electronic media. The Department of Youth, Sports, Culture and Tourism (Disporyata) continues to strive to create culture and tourism with character in the city of Depok. These efforts are carried out by optimizing programs for art development, cultural preservation, and increasing tourism. The purpose of this research is to determine the condition of stand alone venues MICE in Depok City and to find out the efforts of Disporyata in promoting stand alone venues MICE in Depok City. This research was carried out using a qualitative descriptive method based on the results of active field observations, interviews with the parties involved, and the results of documentation during the research. The results of this research are that Disporyata has devised a strategy in promoting independent MICE venues in Depok City, namely creating a website "Nyok Ke Depok" and making a promotional video. Keywords: Promotion, Venue, MICE and Website.